PENGARUH FLUOR DALAM MOUTHWASH TERHADAP GAYA GESER KAWAT STAINLESS STEEL ORTODONTIK - , SANTIKA DEVI ARIMBI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Oral hygiene is one important component of orthodontic treatment accomplishment. Mouthwash containing fluoride is used as an attempt to maintain oral hygiene. The aim of this study was to investigate the effect of fluoride mouthwash on shear force stainless steel orthodontic wire. Research subjects consisted of 20 specimens of stainless steel orthodontic wire diameter of 0.6 mm were divided into 2 groups as control group and exeperiment group. Each group was immersed in acetic acid pH 4.2 and stored in incubator temperature 37Â°C for 5 days. Stainless steel wire was treated 2 times a day morning and evening, immersed for 1 min in 10 ml of mouthwash without fluoride and mouthwash with fluoride, then rinsed with distilled water. On the sixth day stainless steel wire fixed on the acrylic plate and shear force was measured with the tension gauge. Research data was tested by independent t-test. The results showed that there were significant differences (p<0.05) between shear force stainless steel orthodontic wire in fluoride mouthwash and mouthwash without fluoride. The conclusion of this study was fluoride in mouthwashes decrease shear forces on orthodontic stainless steel wire.